An Intra-hippocampal Injection of Nandrolone Induces Learning and Memory Impairments in Rat - Karamian, A.; Pakdel, F. G.; Ilkhanipoor, M.; Farokhi, F.; Ahmadi, A. (Drug Research, 2015)
This study was investigated to evaluate the effect of intra-hippocampal injection of the nandrolone on spatial learning task in rats. The drug or vehicle was manually injected into the hippocampus with a 10-µl Hamilton syringe attached via polyethylene tubing to 27-gauge stainless-steel injection cannula. After 6 days of recovery, learning behaviors were evaluated using an 8-arm radial maze. The results showed that intra-hippocampal injection of nandrolone can impair trained spatial learning at a dose of 5 µl. We also observed a dense cytoplasm and nucleus in CA1 neurons as well as signs of necrosis. Nandrolone can impair the time required to reach the baited arm as well as the frequency of successful arm entries. At the 10 µl dose of nandrolone, neural hypertrophy and increased dentate gyrus volume were also observed.
Keywords: intra-hippocampal; nandrolone; learning; memory; radial maze